Pola Perjalanan Wisata di Air Terjun Benang Kelambu Lombok Tengah - Birru, Rizam Asrori Dyar; Royanow, Achlan Fahlevi; Mahawira, Komang (Contemporary Journal of Applied Sciences, 2024)
In the tourism industry, there is a concept known as travel patterns. This concept has a very important value for managers of tourist destinations or tourist villages in designing travel programs or packages. Travel patterns refer to the sequence of trips from one tourist destination to another interconnected destination, which influences the decisions of tourists. The purpose of this study is to understand how the real conditions of the 5A aspects at Benang Kelambu Waterfall are currently and to find out how to prepare travel patterns based on current conditions at Benang Kelambu Waterfall. The method used in this research is a qualitative method, and the data collection techniques used in this research are several ways, namely Survey, Observation, Interview and Documentation. The data analysis technique in this research is descriptive qualitative analysis method. From the results of this study it is known that the Benang Kelambu Waterfall is adequate in terms of the 5 A aspects (Attractions, Accommodation, Amenity, Activities and Accessibility). And for the preparation of travel patterns in the Pink Thread Waterfall will produce a tourism product in the form of a Travel Pattern Map